2009
DOI: 10.1101/gad.1811209
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from X-chromosome inactivation: long ncRNA as guides and tethers to the epigenome

Abstract: Transcriptome studies are revealing that the eukaryotic genome actively transcribes a diverse repertoire of large noncoding RNAs (ncRNAs), many of which are unannotated and distinct from the small RNAs that have garnered much attention in recent years. Why are they so pervasive, and do they have a function? X-chromosome inactivation (XCI) is a classic epigenetic phenomenon associated with many large ncRNAs. Here, I provide a perspective on how XCI is achieved in mice and suggest how this knowledge can be appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
271
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(281 citation statements)
references
References 119 publications
(177 reference statements)
5
271
1
4
Order By: Relevance
“…The extensive sequence space available to lncRNAs provide plausible strategies for highly discriminative binding to the genome in an allele-or gene-specific fashion (reviewed in ref. 3). Possible RNA targeting schemes include the following (see Fig 1):…”
Section: Mechanisms For Targeting Of Long Noncoding Rnasmentioning
confidence: 99%
“…The extensive sequence space available to lncRNAs provide plausible strategies for highly discriminative binding to the genome in an allele-or gene-specific fashion (reviewed in ref. 3). Possible RNA targeting schemes include the following (see Fig 1):…”
Section: Mechanisms For Targeting Of Long Noncoding Rnasmentioning
confidence: 99%
“…A small subset of those long noncoding RNAs (lncRNAs) have been shown to be essential for a variety of biological processes, such as epigenetic control of chromatin (Rinn et al 2007;Wang et al 2011), promoter-specific gene regulation (Feng et al 2006;Martianov et al 2007), X-chromosome inactivation (Lee 2009;Tian et al 2010), imprinting (Bartolomei et al 1991;Lyle et al 2000), nuclear import (Willingham et al 2005), and maintenance of nuclear body structure (Mao et al 2011). More recently, loss-of-function studies with a large number of lncRNAs expressed in mouse embryonic stem cells showed that lncRNAs regulate gene expression patterns that control pluripotent state or lineage commitment programs in stem cells (Guttman et al 2011).…”
mentioning
confidence: 99%
“…There are several examples of PRC2-recruiting lncRNAs. In mammals, Xist lncRNA coats one of the X chromosome in cis, then the RepA lncRNA recruits PRC2, interacting with Xist and spreading across the chromosome, finally resulting in histone methylation (H3K27m3) and heterochromatin formation [3] (Figure 1A). Another lncRNA, known as HOTAIR, was shown to recruit the PRC2 complex and to silence 40 kb of the HOXD locus [4].…”
Section: Facioscapulohumeral Muscular Dystrophy (Fshd) Is a Neuromuscmentioning
confidence: 99%